2020
DOI: 10.3390/plants9010056
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Major Transcription Factors in Solanaceous Food Crops under Different Stress Conditions: Current and Future Perspectives

Abstract: Plant growth, development, and productivity are adversely affected by environmental stresses such as drought (osmotic stress), soil salinity, cold, oxidative stress, irradiation, and diverse diseases. These impacts are of increasing concern in light of climate change. Noticeably, plants have developed their adaptive mechanism to respond to environmental stresses by transcriptional activation of stress-responsive genes. Among the known transcription factors, DoF, WRKY, MYB, NAC, bZIP, ERF, ARF and HSF are those… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 202 publications
(256 reference statements)
0
28
0
Order By: Relevance
“…Several transcription factors from DoF, WRKY, MYB, NAC, bZIP, ERF, and HSF families, previously associated with abiotic and biotic stress response in Solanaceae [ 11 , 17 ], were found within the QTL regions, some of them with maximum root expression ( Table S6 ). Among them, WRKY transcription factors 2 (Solyc04g078550), 5 (Solyc10g007970), 11 (Solyc08g006320), and 17 (Solyc07g051840), previously related to the drought stress response were found within clusters V, XI, VIII, and VII, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Several transcription factors from DoF, WRKY, MYB, NAC, bZIP, ERF, and HSF families, previously associated with abiotic and biotic stress response in Solanaceae [ 11 , 17 ], were found within the QTL regions, some of them with maximum root expression ( Table S6 ). Among them, WRKY transcription factors 2 (Solyc04g078550), 5 (Solyc10g007970), 11 (Solyc08g006320), and 17 (Solyc07g051840), previously related to the drought stress response were found within clusters V, XI, VIII, and VII, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Since transcription factors participate in activating/repressing gene expression in response to biotic and abiotic stresses, they have been the target of many studies to improve plant stress tolerance [ 11 , 17 ] through reverse genetics. Complementing this strategy, we have found transcription factors belonging to the main families previously associated with the plant stress response (DoF, WRKY, MYB, NAC, bZIP, ERF, ARF, and HSR) in the QTL clusters ( Table S6 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study found that the WLL group was mainly resistant, while the WUL group was mainly tolerant. After mechanical damage, plants still selectively carry out secondary metabolism under resource limitation, inducing related defense compounds, reducing resource utilization in the repository, and showing the importance of secondary metabolism in response to mechanical damage [54,55]. Therefore, damaged C. roseus must be effectively balanced and allocated under limited resources.…”
Section: Discussionmentioning
confidence: 99%
“…Plants respond to different abiotic and biotic challenges through changes at the molecular, cellular, biochemical, and physiological levels. In many cases, the driving forces behind these changes are genes encoding transcription activators and repressors that regulate expression of downstream stress responsive genes and modulate different developmental and metabolic pathways [3]. During the past couple of decades, extensive research has focused on the identification of the key factors associated with regulating the molecular response to stress signal perception [2].…”
Section: Introductionmentioning
confidence: 99%